Construction of Curcumin and Paclitaxel Co-Loaded Lipid Nano Platform and Evaluation of Its Anti-Hepatoma Activity in vitro and Pharmacokinetics in vivo - Wei Y; Wei Y; Sheng L; Ma J; Su Z; Wen J; Li L; Jia Q; Liu H; Si H; Xiong L; Chen J; et al. (International Journal of Nanomedicine, 2023)
Yuxun Wei,1– 4,* Yumeng Wei,1– 4,* Lin Sheng,1– 4 Jingwen Ma,1– 4 Zhilian Su,1– 4 Jie Wen,1– 4 Lanmei Li,5 Qiang Jia,2,6 Huiyang Liu,1– 4 Hui Si,2,4 Linjin Xiong,1– 4 Jinglin Chen,1– 4 Ju Cheng,3,4 Ying Zuo,2,7 Hongru Yang,8 Ling Zhao2– 4 1Key Laboratory of Medical Electrophysiology, Ministry of Education, School of Pharmacy of Southwest Medical University, Luzhou, People’s Republic of China; 2Key Laboratory of Medical Electrophysiology, Ministry of Education, The Affiliated Traditional Chinese Medicine Hospital of Southwest Medical University; Luzhou, Sichuan, People’s Republic of China; 3Central Nervous System Drug Key Laboratory of Sichuan Province, School of Pharmacy of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 4Luzhou Key Laboratory of Traditional Chinese Medicine for Chronic Diseases Jointly Built by Sichuan and Chongqing, The Affiliated Traditional Chinese Medicine Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 5Nanchong Key Laboratory of Individualized Drug Therapy, Department of Pharmacy, Nanchong Central Hospital, The Second Clinical Medical College, North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of China; 6Ethics Committee Office, The Affiliated Traditional Chinese Medicine Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 7Department of Comprehensive Medicine, The Affiliated Traditional Chinese Medicine Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 8Department of Oncology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling Zhao, Key Laboratory of Medical Electrophysiology, Ministry of Education, Luzhou Key Laboratory of Traditional Chinese Medicine for Chronic Diseases Jointly Built by Sichuan and Chongqing, The Affiliated Traditional Chinese Medicine Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China, Tel/Fax +86 830 3160093, Email zhaoling-998@163.com Hongru Yang, Department of Oncology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China, Tel/Fax +86 830 8585668, Email yanghongru801@126.comPurpose: The present study aimed to construct a co-loading platform encapsulating curcumin and paclitaxel at ratios of 2:1– 80:1 (w/w) designated “CU-PTX-LNP” and explored the synergistic effects of CU-PTX at different composite proportions on liver cancer cells using the combination index (CI) method.Methods: The CU lipid nanoplatform (CU-LNP) formulation was optimized via single-factor and orthogonal experiments. Various concentrations of PTX were added to the optimal formulation of CU-LNP to generate CU-PTX-LNP and the nanoplatform characterized via differential scanning calorimetry (DSC), transmission electron microscope (TEM), X-ray diffraction (XRD), zeta potential, polydispersity index (PDI), and size analyses. The cumulative release, stability, and cytotoxicity of CU-PTX-LNP in LO2, HepG2, and SMMC-7221 cells were assessed in vitro, followed by safety investigation and pharmacokinetic studies in vivo. The anti-tumor activity of CU-PTX-LNP was also evaluated using nude mice.Results: CU-PTX-LNP formulations containing CU:PTX at a range of proportions (2:1– 80:1; w/w) appeared as uniformly dispersed nanosized spherical particles with high entrapment efficiency (EE> 90%), sustained release and long-lasting stability. Data from in vitro cytotoxicity assays showed a decrease in the IC50 value of PTX of CU-PTX-LNP (by 5.47– 332.7 times in HepG2 and 4.29– 143.21 times in SMMC-7221 cells) compared to free PTX. In vivo, CU-PTX-LNP displayed excellent biosafety, significant anti-tumor benefits and enhanced pharmacokinetic behavior with longer mean residence time (MRT(0-t); CU: 4.31-fold, PTX: 4.61-fold) and half-life (t1/2z; CU: 1.83-fold, PTX: 2.28-fold) relative to free drugs.Conclusion: The newly designed CU-PTX-LNP platform may serve as a viable technological support system for the successful production of CU-PTX composite preparations.Keywords: curcumin, paclitaxel, lipid nano platform, synergistic effect